Toughened and machinable glass matrix composites reinforced with graphene and graphene-oxide nano platelets - Porwal, Harshit; Tatarko, Peter; Grasso, Salvatore; Hu, Chunfeng; Boccaccini, Aldo R.; Dlouhy, Ivo; Reece, Mike J. (Science and Technology of Advanced Materials, 2013)
The processing conditions for preparing well dispersed silica-graphene nanoplatelets and silica-graphene oxide nanoplatelets (GONP) composites were optimized using powder and colloidal processing routes. Fully dense silica-GONP composites with up to 2.5 vol% loading were consolidated using spark plasma sintering. The GONP aligned perpendicularly to the applied pressure during sintering. The fracture toughness of the composites increased linearly with increasing concentration of GONP and reached a value of ∼0.9 MPa m 1/2 for 2.5 vol% loading. Various toughening mechanisms including GONP necking, GONP pull-out, crack bridging, crack deflection and crack branching were observed. GONP decreased the hardness and brittleness index (BI) of the composites by ∼30 and ∼50% respectively. The decrease in BI makes silica-GONP composites machinable compared to pure silica. When compared to silica-Carbon nanotube composites, silica-GONP composites show better process-ability and enhanced mechanical properties. © 2013 National Institute for Materials Science.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.toughe
Keywords: graphene/graphene-oxide nanoplatelets; mechanical properties; nanocomposites; silica; sintering